ASSESSING SPECIFIC LANGUAGE NEEDS OF NURSING STUDENTS: LECTURERS’ PERSPECTIVE - Mita Nur Aflah; Irma Manda Negara (Universitas Muhammadiyah Makassar, 2025)
Effective communication is essential for safe and compassionate nursing care, yet language proficiency remains a persistent challenge for many nursing students. As healthcare settings grow increasingly complex and interdisciplinary, the ability to navigate both academic and clinical discourse becomes essential. This study explores the specific language needs of nursing students through interviews with English nursing lecturers. The research finding highlights three key areas of language proficiency: communication skills in clinical settings, academic language skills, and terminology proficiency. Lecturers emphasized the necessity for nursing students to master medical vocabulary to enhance patient interactions and interdisciplinary collaboration. Furthermore, the ability to critically engage with academic literature is essential for evidence-based practice, a cornerstone of modern nursing. The study also reveals the importance of practical applications of language skills, particularly through simulation exercises and role-playing, which foster confidence and fluency in clinical communication. By identifying these specific language needs, the research aims to inform curriculum development and instructional strategies, primarily enhancing the preparation of nursing students for their professional roles in a complex healthcare environment. This study underscores the need for targeted language learning to equip future nurses with the skills necessary to provide high-quality patient care.